Microbial Danger Signals Control Transcriptional Induction of Distinct MHC Class I L Lineage Genes in Atlantic Salmon - Svenning, Steingrim; Gondek-Wyrozemska, Agata T.; van der Wal, Yorick Andreas; Robertsen, Børre; Jensen, Ingvill; Jørgensen, Jorunn B.; Edholm, Eva-Stina (Frontiers in Immunology, 2019)
Antigen processing and presentation by major histocompatibility complex (MHC) molecules is a cornerstone in vertebrate immunity. Like mammals, teleosts possess both classical MHC class I and multiple families of divergent MHC class I genes. However, while certain mammalian MHC class I-like molecules have proven to be integral in immune regulation against a broad array of pathogens, the biological relevance of the different MHC class I lineages in fish remains elusive. This work focuses on MHC class I L lineage genes and reveals unique regulatory patterns of six genes (Sasa-lia, Sasa-lda, Sasa-lca, Sasa-lga, Sasa-lha, and Sasa-lfa) in antimicrobial immunity of Atlantic salmon (Salmo salar L.). Using two separate in vivo challenge models with different kinetics and immune pathologies combined with in vitro stimulation using viral and bacterial TLR ligands, we show that de novo synthesis of different L lineage genes is distinctly regulated in response to various microbial stimuli. Prior to the onset of classical MHC class I gene expression, lia was rapidly and systemically induced in vivo by the single-stranded (ss) RNA virus salmonid alpha virus 3 (SAV3) but not in response to the intracellular bacterium Piscirickettsia salmonis. In contrast, lga expression was upregulated in response to both viral and bacterial stimuli. A role for distinct MHC class I L-lineage genes in anti-microbial immunity in salmon was further substantiated by a marked upregulation of lia and lga gene expression in response to type I IFNa stimulation in vitro. Comparably, lha showed no transcriptional induction in response to IFNa stimulation but was strongly induced in response to a variety of viral and bacterial TLR ligands. In sharp contrast, lda showed no response to viral or bacterial challenge. Similarly, induction of lca, which is predominantly expressed in primary and secondary lymphoid tissues, was marginal with the exception of a strong and transient upregulation in pancreas following SAV3 challenge Together, these findings suggest that certain Atlantic salmon MHC class I L lineage genes play important and divergent roles in early anti-microbial response and that their regulation, in response to different activation signals, represents a system for selectively promoting the expression of distinct non-classical MHC class I genes in response to different types of immune challenges.